Genes ptz and idi, Coding for Cytokinin Biosynthesis Enzymes, Are Essential for Tumorigenesis and In Planta Growth by P. syringae pv. savastanoi NCPPB 3335 - Añorga, Maite; Pintado, Adrián; Ramos, Cayo; De Diego, Nuria; Ugena, Lydia; Novák, Ondřej; Murillo, Jesús (Frontiers in Plant Science, 2020)
The phytopathogenic bacterium Pseudomonas syringae pv. savastanoi elicits aerial tumours on olive plants and is also able to synthesize large amounts of auxins and cytokinins. The auxin indoleacetic acid was shown to be required for tumorigenesis, but there is only correlational evidence suggesting a role for cytokinins. The model strain NCPPB 3335 contains two plasmid-borne genes coding for cytokinin biosynthesis enzymes: ptz, for an isopentenyl transferase, and idi, for an isopentenyl-diphosphate delta-isomerase. Phylogenetic analyses showed that carriage of ptz and idi is not strictly associated to tumorigenic bacteria, that both genes were linked when first acquired by P. syringae, and that a different allele of ptz has been independently acquired by P. syringae pv. savastanoi and closely related bacteria. We generated mutant derivatives of NCPPB 3335 cured of virulence plasmids or with site-specific deletions of genes ptz and/or idi, and evaluated their virulence in lignified and micropropagated olive plants. Strains lacking ptz, idi or both produced tumours with average volumes up to 29 times smaller, and reached populations up to two orders of magnitude lower, than those induced by strain NCPPB 3335; these phenotypes reverted by complementation with the cloned genes. Trans-zeatin was the most abundant cytokinin in culture filtrates of NCPPB 3335. Deletion of gene ptz abolished biosynthesis of trans-zeatin and dihydrozeatin, whereas a reduced but significant amount of isopentenyladenine was still detected in the medium, suggesting the existence of other genes contributing to cytokinins biosynthesis in P. syringae. Conversely, extracts from strains lacking gene idi contained significantly higher amounts of trans-zeatin than extracts from the wild-type strain but similar amounts of the other cytokinins. This suggests that Idi might promote tumorigenesis by ensuring the biosynthesis of the most active cytokinin forms, their correct balance in planta, or by regulating the expression of other virulence genes. Therefore, gene ptz, but not gene idi, is essential for the biosynthesis of high amounts of cytokinins in culture; however, both ptz and idi are individually essential for the adequate development of tumours on olive plants by Psv NCPPB 3335.